THE EXISTENCE OF GAYO ART BEYOND ITS TRADITIONAL REALM: AN EXPLORATORY STUDY IN BANDA ACEH: EKSISTENSI KESENIAN GAYO DI LUAR RANAH ADATNYA: STUDI EKSPLORASI DI BANDA ACEH - Syawali, Rahmat; Ismail, Fauzi (The Department of Islamic History and Culture in cooperation with the Center for Islamic History and Culture in Aceh and Malay World Studies (PUSAKA), Universitas Islam Negeri Ar-Raniry Banda Aceh, Aceh, Indonesia, 2023)
Gayo art is one of the folk arts of Aceh originating from Tanoh Gayo, Central Aceh. Gayo art serves as popular entertainment and a means of Islamic missionary for the dissemination and development of Islam in the Banda Aceh region. This art is often featured in weddings, circumcision ceremonies, festivals, and other events. The focused types of art are performance arts, such as Gayo dances (Saman, Bines, Guel, and others), music, and poetry. The research findings indicate that the development of Gayo art in Banda Aceh has progressed after being regularly and systematically showcased several times. Gayo art is popular and appreciated in Banda Aceh because, during performances, it is not only unique and beautiful to witness, but it also involves various forms of artistic attractions such as didong and bersebuku. This captivating attraction draws the attention of the community to organize and attend Gayo art performances held on various art stages in Banda Aceh.